Mediation of the frailty index, the relationship between sleep duration and chronic pain in different body regions: insights from the CHARLS cross-sectional study - Changqing Li; Hong Ding; Lei Zhang; Chao Ma; Caiyun Ma; Hebao Wen; Xiaojiang Zhao (Journal of Orthopaedic Surgery and Research)
Abstract Background Sleep duration and frailty index are knowm to influence chronic pain. However, the manner in which these factors interact to influence chronic pain remains unclear. The present study investigates the link between sleep duration and chronic pain using a cross-sectional design while also examining the potential mediating role of the frailty index. Methods This study incorporated 2015 China Health and Retirement Longitudinal Study (CHARLS) data in a cross-sectional design. Multivariate logistic regression was used to assess the link between sleep and chronic pain, and mediation analysis was used to explore the role played by the frailty index. Results The study comprised 10,321 individuals who were at least 45 years old, of whom 3,051 had at least one site of chronic pain. Seep duration was negatively associated with chronic pain in different body regions. The frailty index was positively associated with these sites, and it mediated the associations between sleep duration and chronic pain in different body regions. Conclusion Sleep duration is negatively correlated with chronic pain, whereas the frailty index is positively correlated with chronic pain in different body regions, potentially serving as a mediating factor. This study highlights the importance of incorporating both sleep duration and the frailty index into chronic pain management strategies.